KOLABORASI MULTIDISIPLIN DAN HIBRIDITAS KREATIF DALAM DESAIN VTUBER SEBAGAI MEDIA KOMUNIKASI VISUAL IMERSIF PENGENALAN KAMPUS - Ajeng Tita Negoro; Nurhadi Nurhadi (Journal of Animation and Games Studies, 2026)
The VTuber (Virtual YouTuber) phenomenon has emerged as an innovative interactive visual communication design agent in the multiplatform digital era. This research aims to examine VTubers as a manifestation of creative hybridity that integrates character design, interactive digital animation technology, and visual communication strategies, focusing on the design of the VTuber character "Mayuh Isthika." This character was developed through multidisciplinary collaboration to introduce Telkom University Purwokerto campus in an engaging and immersive manner to prospective students. The research problem formulation in this research is the need for innovative campus introduction media that can attract the interest of the younger generation through the integration of art and technology. The research method applies a qualitative-descriptive approach through a design case study. The development process includes conceptualizing a visual identity based on Banyumas local wisdom, creating illustrations and rigging for 2D animation (Live2D), and designing a narrative-interactive content strategy for social media. Key findings indicate that "Mayuh Isthika" successfully established a strong and interactive campus visual identity. Locally-inspired character designs, combined with real-time animation and two-way narrative, proved effective in increasing audience engagement and strengthening the campus' promotional appeal. This research demonstrates that VTubers can serve as an innovative visual communication medium, combining elements of illustration, animation, and digital technology, creating an immersive, cross-platform, and relevant communication experience within today's popular culture.